Analyzing the strategies used in media discourse management - Brzozowska, Anna; Kalinichenko, Anonina; Kabus, Judyta (Eastern-European Journal of Enterprise Technologies, 2015)
Digital economy is based on digital revolution and information management that gave rise to the new media image in the era of globalization. Media and media discourse management is a completely new concept for establishing innovative relations between manufacturer and consumer. The subject of interest of the present article is the analysis of the existing strategies in media discourse management. The introduction concerns the etymological meanings of the notion of discourse and its application. The main objective of the study is to reveal the capacity of media discourse management in expanding the consumers’ cognitive resources and maintaining stable information links in everyday life. The author aims at generalizing the main problems related to the scope and subject of media and media discourse management. Linguistic genetics and media management were applied as key methods in the study of Polish, German and English media resources.